Features measurement and reliability considerations on a proposed main converter for LHC experiments. (July 2015) - Lazzaroni, M.; Citterio, M.; Latorre, S.; Lanza, A.; Cova, P.; Delmonte, N.; Giuliani, F.
Highlights: Devices operating in the harsh environment are called to work at high level of radiation. Hostile environment for electronic devices is characterized by high level of radiation and magnetic field. Equipment devoted to generate the supply for the electronic circuits can operate in hostile environment. Proposed architecture for the Main Converter is based on SILC topology. Results of the experimental activity have been presented. Abstract: Equipment working in hostile environment are the aim of this paper. Devices operating in the hostile environment such as found in future experiments at LHC will be called to work with a level of background radiation able to cause accumulation of a Total Ionizing Dose (TID) up to 10 kGy in Silicon, and fluences up to 2 × 10 13 protons/cm 2 and 8 × 10 13 neutrons/cm 2 but also a high level of magnetic field. This new scenario will be taken into account and it will be very important in future when the High Luminosity (HL) LHC will be operative. It is so important, at this aim, to consider the fact that also the electronic converters devoted to generate the supply for the electronic circuits can be often called to operate in hostile environment. Thus, the power supply is a key aspects in this scenario and new converters need to be ad-hoc re-designed in order to meet the future requirements that will be very stringent. In this paper a main DC–DC power converter, developed by authors in the framework of the APOLLO R&D project, has been proposed. The experimental activity devoted to its electrical and thermal characterization, which can be defined as mandatory in order to obtain an evaluation of the features, is presented and deeply discussed. It is also important to characterize the system in order to evaluate the dependability features such as the RAMS (Reliability, Availability, Maintainability Safety) requirements. In particular, reliability is a very important aspect in experiments as ATLAS at CERN where maintenance should be scheduled only during the shutdown time. Also these aspects have been considered and discussed in the paper.